Excitatory Repetitive Transcranial Magnetic Stimulation Over the Ipsilesional Hemisphere for Upper Limb Motor Function After Stroke: A Systematic Review and Meta-Analysis - Tang, Zhiqing; Han, Kaiyue; Wang, Rongrong; Zhang, Yue; Zhang, Hao (Frontiers in Neurology, 2022)
Background:rTMS is a promising therapy to promote recovery of the upper limb after stroke. According to the regulation of cortical excitability, rTMS can be divided into excitatory rTMS and inhibitory rTMS, and excitatory rTMS includes HF-rTMS or iTBS. We aimed to evaluate the effects of excitatory rTMS over the ipsilesional hemisphere on upper limb motor recovery after stroke.Methods:Databases of PubMed, Embase, ISI Web of Science, and the Cochrane Library were searched for RCTs published before December 31, 2021. RCTs on the effects of HF-rTMS or iTBS on upper limb function stroke patients were included. Two researchers independently screened literature, extracted the data, and assessed quality. The meta-analysis was performed by using the Review Manager Version 5.4 software.Results:Fifteen studies with 449 participants were included in this meta-analysis.This meta-analysis found excitatory rTMS had significant efficacy on upper limb motor function (MD=5.88, 95% CI, 3.32 to 8.43, P<0.001), hand strength (SMD=0.53, 95% CI, 0.04 to 1.01, P=0.03) and hand dexterity (SMD=0.76, 95% CI, 0.39 to 1.14, P<0.001). Subgroup analyses based on different types of rTMS showed both iTBS and HF-rTMS significantly promoted upper limb motor function (iTBS, P < 0.001; HF-rTMS, P<0.001) and hand dexterity (iTBS, P=0.01; HF-rTMS, P<0.001), but not hand strength (iTBS,P=0.07; HF-rTMS, P=0.12). Further subgroup analysis based on the duration of illness demonstrated applying excitatory rTMS during the first 3 months (< 1 month,P=0.01; 1-3 months,P=0.001) after stroke brought significant improvement in upper limb motor function, but not in the patients with a duration longer than 3 months (P = 0.06). We found HF-rTMS significantly enhanced MEP amplitude of affected hemisphere (SMD=0.82,95% CI,0.32 to 1.33, P=0.001).Conclusion:Our study demonstrated that excitatory rTMS over the ipsilesional hemisphere could significantly improve upper limb motor function, hand strength and hand dexterity in stroke patients. Both iTBS and HF-rTMS could significantly promote upper limb motor function and hand dexterity, and excitatory rTMS were beneficial to upper limb motor function recovery when only applied in the first 3 months after stroke. HF-rTMS could significantly enhance the MEP amplitude of affected hemisphere. High-quality and large-scale randomized controlled trials in the future are required to confirm our conclusions.